2019
DOI: 10.12669/pjms.35.6.990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altering the regime of oral rifampicin therapy in the treatment of persistent central serous chorioretinopathy

Abstract: Objective: To study the effect of reducing the duration of rifampicin therapy in the treatment of Chronic Central Serous Chorioretinopathy. Methods: This is interventional study conducted in Layton Rahmatullah Benevolent Trust, Free Base Eye Hospital Korangi, Karachi from February 2017 - December 2018. This randomized controlled comparative study included two groups, Groups-A comprised of 48 eyes of 40 cases with Chronic Central Serous Chorioretinopathy who were given reduced dose of oral rifampicin i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Contrastingly, Golshahi et al found that a month-long administration of 200 mg ketoconazole per day did not surpass the effects of placebo treatment [24]. A few studies reported resolution of the subretinal fluid in patients with CSC following the administration of oral rifampin [27][28][29]. Rifampin is a cytochrome P450 and 3A4 inducer and thus increases the processing of endogenous steroids through the induction of hepatic metabolism [34,35].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Contrastingly, Golshahi et al found that a month-long administration of 200 mg ketoconazole per day did not surpass the effects of placebo treatment [24]. A few studies reported resolution of the subretinal fluid in patients with CSC following the administration of oral rifampin [27][28][29]. Rifampin is a cytochrome P450 and 3A4 inducer and thus increases the processing of endogenous steroids through the induction of hepatic metabolism [34,35].…”
Section: Resultsmentioning
confidence: 98%
“…Given that corticosteroids are involved in CSC formation, glucocorticoid inhibition has been recommended as a possible therapeutic method [16][17][18][19][20][21][22]. Small-scale case series support the role of systemic anti-corticosteroid agents, including mifepristone, ketoconazole, finasteride, and rifampin, in the treatment of CSC [6,[23][24][25][26][27]. A few studies recently examined the impacts of mineralocorticoid receptor antagonists on CSC and endorsed the use of these agents in treating the disease [28][29][30], but these medications have not been included in the treatment protocols for CSC.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies investigated efficacy of other types of therapies. Loya et al (2019) studied the effect of oral rifampicin 600 mg daily for 1 month and compared with a group who received oral rifampicin 300 mg daily for 3 months. The authors found no differences between these two dosages in terms of efficacy (Loya et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…treatment of low‐fluence PDT at 30% vs. 40% vs. 50%). In addition, Loya et al (2019) were also excluded from the analyses since none of the other studies had a rifampicin treatment group, Loya et al (2019) did not have another treatment or control study group, and hence, the network did not reach out to this study. In total, 16 studies were eligible for the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation